ANALYSIS OF ONLINE MEDIA LIVE STREAMING TRENDS ON WEBSITES AND YOUTUBE NEWS TELEVISION IN WEST JAVA - Mirza Ronda; Geofakta Razali (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
The increasing adoption of online live streaming by most news television in West Java is utilized as one of the online broadcasting media. This research was conducted using a qualitative approach and meta-analytic method from data from one of the private news television stations in West Java. The results of the analysis show that the trend of using online live streaming on websites and Youtube to get news information continues to increase and allows users to adopt online broadcasts more than conventional ones which will also trigger business shifts and media convergence in West Java.